Fate of pharmaceuticals during membrane bioreactor treatment: Status and perspectives. (November 2018) - Gu, Yanling; Huang, Jinhui; Zeng, Guangming; Shi, Lixiu; Shi, Yahui; Yi, Kaixin
Graphical abstract: Highlights: Recent studies on pharmaceuticals removal in MBR treatment process are reviewed. MBR process and operation parameters have effects on pharmaceuticals removal. Degradation mechanism of pharmaceuticals and transformation product are analyzed. Pharmaceuticals are adsorbed by sludge, membrane, and exogenous substance. Knowledge gaps and recommendation for future research needs are proposed. Abstract: Pharmaceuticals in surface waters and wastewater treatment plants (WWTPs) as emerging pollutants have become a major concern. In comparison with other wastewater treatments, removal of pharmaceuticals in MBR has received much attention. This review presents the source and occurrence of pharmaceuticals in WWTPs influents. Experimental studies related to the removal of pharmaceuticals during MBR treatment, key affecting factors (including the different stages of MBR process configuration and the process parameters), and the underlying mechanisms proposed to explain the biodegradation and adsorption behaviors, have been comprehensively discussed. Several transformation products of pharmaceuticals are also reviewed in this paper. Furthermore, further research is needed to gain more information about the multiple influence factors of the pharmaceuticals elimination, appropriate methods for promoting pharmaceuticals elimination, more essential removal pathways, effect of pharmaceuticals on membrane fouling, and the detection and analysis of transformation products.